The Impact of Problem-Based Learning and HOTS Based Formative Tests on Critical Thinking - Ismail, Nauval Syafiq; Mertasari, Ni Made Sri; Widiartini, Ni Ketut (International Journal of Humanities, Education, and Social Sciences, 2025)
This research aims to examine the impact of the Problem-Based Learning (PBL) model and the use of formative tests designed to assess Higher Order Thinking Skills (HOTS) on students' critical thinking abilities. A quasi-experimental design with a Nonequivalent Control Group Design was used, involving two groups: the experimental group employing the PBL model and the control group using traditional teaching methods. Data were gathered through oral and essay tests to evaluate students' critical thinking skills. The findings indicate that the PBL model has a significant positive effect on improving students' critical thinking. Moreover, the use of HOTS-based formative tests was found to significantly enhance students' critical thinking abilities. The combination of the learning model and the type of formative test produced the most considerable improvement in critical thinking skills within the experimental group. The study recommends that teachers expand the use of the PBL model and incorporate HOTS-based assessments to foster critical thinking, which is vital for preparing students to tackle global challenges.